Aplikasi Pupuk Kandang Pada Tanah Merah (Ultisol Soil) Di Lahan Pertanian Batam, Kepulauan Riau - Mia Juliana Siregar; Adi Nugroho (Fakultas Teknik, 2021)
Ultisol soil is a less fertile soil characterized by low soil fertility rate, high acidity with pH5, high Al saturation. This land has an area of 25% of the total land area of Indonesia. Riau Island is one of the provinces dominated by Ultisol land, so many land is not productive to use as agricultural land. This research was conducted to look at the characteristics of red soil in the agricultural land in Batam City after mixed with organic material in this case which is used is goat manure and chicken manure. From the results of research, the addition of goat manure and chicken manure that is incubated for 30 days can already give changes to the physical and chemical character of the soil, such as soil becoming more loose, having higher water content, increasing soil C organic, Nitorgen, P2O5, K, Mg, and Mn, able to reduce Fe levels in the soil. The addition of chicken manure can increase the available of Phosphate, gives K, Mg, and Mn higher than compared mixing blanko with goat manure. The addition of goat manure can increase the total of C organic and N in the soil is higher than chicken manure.